Rancang Bangun Sistem Informasi Daftar Menu Studi Kasus Outlet Kopi Kenangan SPBU Cikini Berbasis Web - Nugroho, Ristyanto Adi; Sharyanto, Sharyanto; Bani, Alexius Ulan (Yayasan Bina Internusa Mabarindo, 2024)
In the rapidly evolving digital era, the implementation of computerized information systems has become an essential requirement for various business sectors, including the culinary industry. Kopi Kenangan, operating at the Cikini Gas Station since 2017, has seen an increase in the number of customers. However, the process of determining and managing the menu is still done manually, resulting in inefficiencies and high paper usage. To address these issues, this study aims to design and develop a web-based menu information system at the Kopi Kenangan outlet at the Cikini Gas Station. The system is expected to enhance efficiency in menu management and improve customer satisfaction. The methodology used in this study includes system requirements analysis, system design using UML, and implementation using PHP and MySQL technologies, in addition to developing the application using the waterfall method. The result of this study is an information system that facilitates menu management, reduces errors, and speeds up the process of updating menu information at the Kopi Kenangan outlet.